Film ‘The Candle’ Sebagai Literasi Media Kasus Maraknya Guru Yang Dipidanakan - Nur Aini Shofiya Asy'ari (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2017)
The media has a major influence on the dissemination of information and the formation of public opinion on issues emerging in society. Even the continued problems of certain issues in society may be the impact of the magnitude of media influence itself. Media framing in packing news leads people to certain trends in attitude. The incessant media coverage of the criminalization of teachers violating the Child Protection Act (UU) No.23 of 2002 even triggered more similar cases in other places. Communities may be inspired to report to teachers even if the teacher’s actions do not include child abuse and are merely educational measures. Another impact is the deterioration of teachers’ authority and the decrease in school credibility. An intense media coverage of an issue must be balanced with good media literacy. Currently, there has been a lot of media literacy movements, but still few use film as a medium for media literacy, whereas film is a very effective medium for expressing messages and influencing others as Quick and La Bau (1972: 11) say. The Candle film is the work of UNIDA Gontor Communication Studies students created with the goal of providing media literacy to the public. There were significant results in the change of mindset and attitude of the students, teachers and guardians as the target of media literacy by using The Candle film.